Value chain development to reach the nutritional needs of the urban poor: The role of brokers and SMEs for the commercialization of common beans in East Africa - Wilkus, Erin Lynn; Francesconi, Gian N. (International Center for Tropical Agriculture, 2017)
This study addresses the need to empirically determine the effect of brokers on the performance of SMEs in the common bean value chains of Uganda and Kenya. Contrary to the conventional portrayal of brokers as scam artists, this analysis determined that broker use benefited SMEs by increasing profit margins of bean traders, wholesalers and retailers along the value chain.